Cultural predictions of entrepreneurial orientation and the moderating role of entrepreneurial competencies on graduate entrepreneurial intentions: A cross-sectional survey of East Africa - Katono, Isaac Wasswa (School of Management Studies, 2021)
This research project examines a theoretical gap (impact of culture on entrepreneurial orientation EO) to try and mitigate a practical problem (unemployment) among graduates in three East African countries: Kenya, Tanzania and Uganda. Unemployment would be mitigated if only graduates embraced entrepreneurship by starting their own business projects, and many governments have encouraged their youth/graduates to do this. Unfortunately, graduate student interest in entrepreneurial activities in many countries in Africa is very low, and the three study countries are no exception to this trend. While many explanations have been advanced for this phenomenon, a key theoretical gap left unattended in entrepreneurship research is the way in which culture impacts upon EO and how this affects entrepreneurial intention (EI), yet EO is often considered the most important variable in the formative stage of a given project. A close look at how culture influences EO is important because EO is unexplainable without considering the socio-cultural framework in which it is embedded, since it can be supportive or a hindrance to entrepreneurship in different contexts. Thus the key question which this study tries to address is: „Does culture constrain the development of a strong EO, eventually leading to low start-up in this region?‟ Specifically, can the low graduate start-up in these countries be explained by the impact of five cultural orientation dimensions (ambiguity intolerance, power distance, masculinity, independence and interdependence) and ability perception variables (achievement motivation and learning goal orientation LGO) on two variables of EO namely risk taking and proactiveness? How does gender affect these relationships? Besides gender, this study also sought to know the level of prevalence in the study population of three other important culturally influenced variables in entrepreneurship literature namely experience, fear of failure and modernity in order to throw more light on the study problem In particular, given that individuals with a modern outlook are somehow liberated from firm cultural norms, this study sought to establish whether students with a more modern outlook differ from those with a less modern one in terms of the study variables. Further, does optimism another important culturally inclined characteristic of entrepreneurs moderate the relationship between EO and entrepreneurial intention? Some authors argue, however, that culture does not matter; rather, what matters are the entrepreneurial competencies of an entrepreneur. Hence another major question addressed in the current study is to what extent do entrepreneurial competencies (such as knowledge/networks) moderate the relationship between EO and entrepreneurial intention? Using the theory of planned behavior (TPB), upper echelons theory and image theory, this study seeks to address these questions based on a pragmatic paradigm and thus a mixed methods approach in two phases. Phase one of the study was qualitative consisting of non- structured interviews and conversations with various stake holders and is the basis upon which the study instrument was refined. Phase two was quantitative, utilizing a cross-sectional survey research design based on a non random sampling to gather data from finalists in business faculties in three public and two private universities in the study countries (N=1086) during their classes. Data analysis consisted of three phases, comprising ten steps. Phase one was more of a preliminary analysis and consisted of five steps: Generation of descriptive statistics such as frequencies, percentages, and normality tests in step 1, T-tests to gauge the prevalence of experience, fear of failure, and modernity as well as a MANOVA to gauge the prevalence of the cultural dimensions in each study country in step 2, Exploratory factor analysis (EFA) by Varimax/promax rotation to examine the factor structures of the study dimensions in step 3, followed by examination of validity (construct validity, discriminant validity) and reliability for all study instruments (alpha and composite reliability, CR) in Step 4, while step 5 confirmed the factor structure of the measures using confirmatory factor analysis CFA (Lisrel 8.8). The second phase utilized structural equation modeling (SEM) based on latent variables (using AMOS 23) to first estimate a CFA model, followed by a structural baseline model for all data combined (omnibus model) in step 6. This was followed by fitting the baseline model into each country data set in step 7. In step 8, data was divided by gender into male and female samples and by modernity into low and high modernity groups and the baseline model was fitted into each of these four data sets. This was followed by invariance tests between the gender sets and modernity sets as a basis for their meaningful comparison (step 9). The third phase utilized the process macro in SPSS (step 10) to conduct the moderation analysis. Study findings indicate that in all three countries, only 50% of the respondents had some sort of start-up experience. A third (31%) of the students in the three countries indicated that fear of failure would prevent them from starting a business, while the rest indicated that it would not. Further, students who do not regard fear of failure as a barrier to entrepreneurial activities scored significantly higher on proactiveness, knowledge, achievement motivation and modernity in all the three countries, while in at least two of these countries, these people scored significantly higher on risk taking, networking and learning goal orientation. This finding confirms that fear of failure is an important barrier to graduate entrepreneurship in this region. Turning to the structural models in SEM, findings indicate that the low start-up rate in these countries can be attributed to the negative impact of ambiguity intolerance (the most problematic variable), power distance, and lack of an optimistic bias as well as possible negative attitude towards those with an independent cultural orientation. However, Independence and Interdependence support EO, in agreement with researchers who assert that both cultural variables are good for entrepreneurship. Theoretically, the study makes an extension of the TPB since achievement motivation predicts intention in all study samples (apart from Kenya and Tanzania). In terms of gender, there are no significant differences on the reported levels of risk taking; however females score significantly higher on proactiveness. Further structural models indicate that males are more achievement oriented than females, while the low modernity group seems to be more entrepreneurial than the high modernity group. Lastly, networks and knowledge moderate the relationship between risk taking/proactiveness and intention, while optimism does not. The study calls for a revision of the curriculum to include tolerance for ambiguity, proactiveness and autonomy courses in entrepreneurship education as well as a change in the mode of delivery of this subject. A transformation in the education systems of the three countries is needed to produce critical thinkers and to introduce entrepreneurship early in the education system to make everyone appreciate entrepreneurship, thus nurturing an entrepreneurial culture.